Biosynthesis and characterization of antibacterial thermosensitive hydrogels based on corn silk extract, hyaluronic acid and nanosilver for potential wound healing. (1st November 2019) - Makvandi, Pooyan; Ali, Ghareib W; Della Sala, Francesca; Abdel-Fattah, Wafa I.; Borzacchiello, Assunta
Highlights: Corn silk extract was used for the green synthesis of Ag nanoparticles. Hyaluronic acid improved the viscoelastic and biological properties of the gels. The nanocomposites gels exhibited good mechanical properties and Tgel close to Tbody . The injectable gels allow fast wound closure and repair and good biocompatibility. Abstract: The wounds closure after physical injury or surgery is of significant clinical and research importance. In this study, thermosensitive and injectable hydrogels based on hyaluronic acid (HA), corn silk extract (CSE) and nanosilver were prepared and their potential use as a wound care material was investigated. Silver nanoparticles (Ag NPs) were biosynthesized by a microwave-assisted green technique using corn silk extract in an organic solvent-free medium. Rheological analysis demonstrated that the nanocomposites have good mechanical properties with gelation temperature close to the body temperature; hence, they can be easily administrated locally on wounded skins. The samples exhibited antibacterial activity toward gram-positive and gram-negative bacteria. Cytotoxicity assay showed that the hydrogels have good biocompatibility. Interestingly, an in-vitro model of wound healing revealed that the nanocomposites allow faster wound closure and repair, compared to the control. The obtained results highlight the potential application of these novel injectable hydrogels as wound dressing.